2011
DOI: 10.1002/bit.23297
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate model of ErbB network composition predicts ovarian cancer cell response to canertinib

Abstract: Identifying the optimal treatment strategy for cancer is an important challenge, particularly for complex diseases like epithelial ovarian cancer (EOC) that are prone to recurrence. In this study we developed a quantitative, multivariate model to predict the extent of ovarian cancer cell death following treatment with an ErbB inhibitor (canertinib, CI-1033). A partial least squares regression model related the levels of ErbB receptors and ligands at the time of treatment to sensitivity to CI-1033. In this way,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
3
19
0
Order By: Relevance
“…For instance, multivariate systems biology approaches that consider multiple proteins, signalling pathways, cell types and tissues can accurately recapitulate and predict therapeutic responses [310][311][312][313]. Recently, there has been a call for the inclusion of interpatient variability into these models [312].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, multivariate systems biology approaches that consider multiple proteins, signalling pathways, cell types and tissues can accurately recapitulate and predict therapeutic responses [310][311][312][313]. Recently, there has been a call for the inclusion of interpatient variability into these models [312].…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate how PLSR can be used to analyze a systems-level problem, research utilizing PLSR to identify a predictive relationship between the abundance of members of the epidermal growth factor receptor family ErbB signaling network and sensitivity to an ErbB inhibitor in ovarian cancer cells (OvCa) (17). Although receptors of the ErbB type and their ligands are present in many ovarian cancers, only a subset of patients have responded to ErbB-targeted therapies in clinical trials (18).…”
Section: Lecture Notesmentioning
confidence: 99%
“…Although prior studies have identified univariate biomarkers (for example overexpression of specific genes in the pathway or mutations in those genes) that predict response to these drugs in other tumor types, these markers have not been able to predict therapeutic response in ovarian cancer. Because the ErbB system is composed of four receptors that homo- and hetero-dimerize in response to stimulation by a family of thirteen ligands, Prasasya, et al utilized PLSR to examine if the quantitative balance of the abundance of these ErbB network components could be used to determine which ovarian cancer cells would be sensitive to canertinib (CI-1033), a pan-ErbB inhibitor (17) (Slide 18).…”
Section: Lecture Notesmentioning
confidence: 99%
“…Instead, they act as hubs within a ligand-driven network in which all possible ErbB homo-and/ or heterodimers may occur (15). Substantial evidence points toward the operation of complex integrated ErbB signaling within EOC (16). Coexpression of two or more ErbB receptors is prevalent in this tumor, often together with autocrine ErbB ligand production (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Substantial evidence points toward the operation of complex integrated ErbB signaling within EOC (16). Coexpression of two or more ErbB receptors is prevalent in this tumor, often together with autocrine ErbB ligand production (16)(17)(18)(19)(20). Furthermore, a variety of ErbB heterodimers has been shown to enhance proliferation of EOC tumor cells (20,21).…”
mentioning
confidence: 99%